Biomechanics of Pediatric Manual Wheelchair Mobility - Slavens, Brooke A.; Schnorenberg, Alyssa J.; Aurit, Christine M.; Tarima, Sergey; Vogel, Lawrence C.; Harris, Gerald F. (Frontiers in Bioengineering and Biotechnology, 2015)
Currently, there is limited research of the biomechanics of pediatric manual wheelchair mobility. Specifically, the biomechanics of functional tasks and their relationship to joint pain and health is not well understood. To contribute to this knowledge gap, a quantitative rehabilitation approach was applied for characterizing upper extremity biomechanics of manual wheelchair mobility in children and adolescents during propulsion, starting and stopping tasks. A Vicon motion analysis system captured movement, while a SmartWheel simultaneously collected three-dimensional forces and moments occurring at the hand-rim. A custom pediatric inverse dynamics model was used to evaluate three-dimensional upper extremity joint motions, forces and moments of 14 children with spinal cord injury (SCI) during the functional tasks. Additionally, pain and health-related quality of life outcomes were assessed. This research found that joint demands are significantly different amongst functional tasks, with greatest demands placed on the shoulder during the starting task. Propulsion was significantly different from starting and stopping at all joints. We identified multiple stroke patterns used by the children, some of which are not standard in adults. One subject reported average daily pain, which was minimal. Lower than normal physical health and higher than normal mental health was found in this population. It can be concluded that functional tasks should be considered in addition to propulsion for rehabilitation and SCI treatment planning. This research provides wheelchair users and clinicians with a comprehensive, biomechanical, mobility assessment approach for wheelchair prescription, training, and long-term care of children with SCI.